Australian Government claims 'sophisticated' attack by nation-state actors. Issue 7 (July 2020) - Unknown
Abstract : Australian Prime Minister Scott Morrison has warned of a campaign of attacks against government and commercial organisations in Australia. Without naming names, he has also insisted that the attacks are the work of nation-state entities.